2014
DOI: 10.2337/db14-0625
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Saturable Nature of Signaling Pathways Induced by Metreleptin in Humans: Comparative Evaluation of In Vivo, Ex Vivo, and In Vitro Administration

Abstract: Signaling pathways activated by leptin in metabolically important organs have largely been studied only in animal and/or cell culture studies. In this study, we examined whether leptin has similar effects in human peripheral tissues in vivo, ex vivo, and in vitro and whether the response would be different in lean and obese humans. For in vivo leptin signaling, metreleptin was administered and muscle, adipose tissue, and peripheral blood mononuclear cells were taken for analysis of signal activation. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Three proteins were targets for at least one existing drug that has completed phase II clinical trials (Supplementary Data 15 ). Drugs likely for treating obesity included Metreleptin 31 , which targets leptin receptors, to treat complications of leptin deficiency in individuals with congenital or acquired lipodystrophy. Another drug, Pegvisomant 32 , is a highly selective growth hormone (GH) receptor antagonist that is used to treat acromegaly by the production of IGF-1 which is the main mediator of GH activity.…”
Section: Resultsmentioning
confidence: 99%
“…Three proteins were targets for at least one existing drug that has completed phase II clinical trials (Supplementary Data 15 ). Drugs likely for treating obesity included Metreleptin 31 , which targets leptin receptors, to treat complications of leptin deficiency in individuals with congenital or acquired lipodystrophy. Another drug, Pegvisomant 32 , is a highly selective growth hormone (GH) receptor antagonist that is used to treat acromegaly by the production of IGF-1 which is the main mediator of GH activity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the lack of leptin efficacy in human obesity is due to the development of central leptin resistance or tolerance in parallel with increased circulating leptin levels upon and before obesity development [21]. Leptin signaling pathways, the abnormality of which may eventually lead to the development of leptin resistance, have only recently started to be studied in humans [116][117][118][119][120][121]. In the search for agents that may restore leptin sensitivity, amylin (pramlintide) has been shown to induce weight loss in obese rodent models and humans when given together with leptin [122].…”
Section: Leptinmentioning
confidence: 99%
“…as Janus kinase 2-signal transducer and activator of transcription 3 (JAK2-STAT3) (21,22,23), insulin receptor substrate (IRS)-phosphatidylinositol 3 kinase (PI3K) (24), SH2-containing protein tyrosine phosphatase 2 (SHP2)-mitogen-activated protein kinase (MAPK) (25) and 5′ adenosine monophosphate activated protein kinase (AMPK) -acetyl-CoA carboxylase (ACC) (26). The aforementioned molecular signaling pathways regulate energy homeostasis, anorectic/orexigenic pathways, glucose and fatty acid metabolism, insulin secretion and activation of cellular proliferation pathways (21,24,27,28).…”
Section: Leptin Biologymentioning
confidence: 99%